2017
DOI: 10.1177/0014402917736261
|View full text |Cite
|
Sign up to set email alerts
|

Suicidality and Intersectionality Among Students Identifying as Nonheterosexual and With a Disability

Abstract: Research about students with disabilities and students identifying as LGBQ (lesbian, gay, bisexual, or questioning) reveals that both populations report more suicidality and peer victimization and less school connectedness than do their peers. No study has previously examined the intersection of these identities with regard to peer victimization, school connectedness, and suicidality. Using a sample of 11,364 high school students, we examined the relationships among these identities, peer victimization, and sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 44 publications
0
33
0
1
Order By: Relevance
“…Although there is no one age that a student may “come out,” there is research to support that youth of all ages who do not express a heteronormative or cisgender identity are at greater risk of victimization in school (Kosciw, Greytak, Palmer, & Boesen, 2014) as well as suicidal ideation (King, Merrin, Espelage, Grant, & Bub, 2018). In addition, youth who identify as lesbian, gay, bisexual, transgender, queer or questioning (LGBTQ) are known to be at risk of more distal negative outcomes (e.g., depression, dropping out of high school; Kosciw et al, 2014), and youth with disabilities experience unique experiences due to their identities around ability status and sexuality (Kahn & Lindstrom, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no one age that a student may “come out,” there is research to support that youth of all ages who do not express a heteronormative or cisgender identity are at greater risk of victimization in school (Kosciw, Greytak, Palmer, & Boesen, 2014) as well as suicidal ideation (King, Merrin, Espelage, Grant, & Bub, 2018). In addition, youth who identify as lesbian, gay, bisexual, transgender, queer or questioning (LGBTQ) are known to be at risk of more distal negative outcomes (e.g., depression, dropping out of high school; Kosciw et al, 2014), and youth with disabilities experience unique experiences due to their identities around ability status and sexuality (Kahn & Lindstrom, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In relation to suicidal ideation, King and colleagues (2018) found that disabled students as defined by IDEA definitions and students identifying as lesbian, gay, bisexual, or questioning (LGBQ) exhibit higher levels of suicidality and peer victimization and less school connectedness in comparison with their peers. In fact, students with the highest levels of suicidal ideation were those who identified as disabled and LGBQ (King et al, 2018). On the contrary, other research has showed that suicidality was viewed as more socially acceptable in relation to disability, meaning that the presence of disability was viewed as an appropriate reason to commit suicide, when adult participants were presented with vignettes discussing suicidal ideation and comparisons were made between the disability and no-disability conditions (Lund et al, 2016).…”
Section: Suicidal Ideationmentioning
confidence: 99%
“…This study focuses on discriminatory bullying based on individual differences associated with a disability or special educational needs. Three out of ten teenagers are involved in this type of discriminatory bullying (Rodríguez-Hidalgo, Alcívar, et al, 2019), whose devastating effects impact the academic performance of these children and adolescents, as well as the general socializing process (Ashburner et al, 2019), psychological well-being (Chiu et al, 2018;Paul et al, 2018;Pérez-Garín et al, 2018), and suicidal ideation (King et al, 2018).…”
Section: Extended Summarymentioning
confidence: 99%
“…Otra investigación concluye que el bullying discriminatorio tiene consecuencias más graves que el bullying tradicional o personal (Salmon et al, 2018), así como efectos más prolongados y en algunos casos para toda la vida (Earnshaw et al, 2018). Un alto nivel de victimización discriminatoria se relaciona con un nivel bajo de asistencia, participación y rendimiento en la escuela (Ashburner et al, 2019), con un nivel bajo de satisfacción con la vida, equilibrio afectivo y bienestar psicológico (Chiu et al, 2018;Paul et al, 2018;Pérez-Garín et al, 2018) y, desgraciadamente, con un nivel elevado de ideación suicida (King, et al, 2018). Esta línea de investigación incluye también la violencia discriminatoria con los escolares de orientación sexual diversa, como la victimización homofóbica (p.…”
unclassified